Alternative and complementary treatments in women with breast cancer - Humańska, Marzena A.; Nowicki, Andrzej (Contemporary Oncology/Współczesna Onkologia, 2005)
Breast cancer is the most common cancer among Polish women. In 2000, 10987 new cases of female breast cancer were diagnosed. Breast cancer treatments are constantly changing. Aside from conventional medicine, patients tend to use complementary and alternative medicine. National Health Institutes classify complementary treatments as therapies used together with the conventional treatment, whereas alternative medicine is classified as one used instead of conventional methods. Unconventional medicine is more often used by women with breast cancer than by patients with other types of cancer. Women who use complementary treatments are more optimistic and have a stronger sense of control of their situation. Sincere interest in patient’s complaints and his life is a common feature shared by most natural methods. Direct contact and a conversation directed at the most important problems are comforting to the patient. Alternative medicine methods are difficult to assess. Relations between researchers and doctors using alternative methods are often tense because the latter do not trust the researchers’ motives. Professor of Harvard University and the head of the National Cancer Institute believe that the integration of conventional and alternative medicine is essential. Two fundamental rules of cooperation have been formulated. The first rule tells about the mutual respect while the second reminds doctors and researchers that they must also respect facts. A blend of conventional and alternative medicine may improve health in the society and increase the curability rate. It seems that alternative medicine should no longer be ignored.